Factors Affecting Consumer Satisfaction with Mixue Products in Pasuruan - Faizatul Mukarromah; Wenny Mamilianti (Universitas Muhammadiyah Malang, 2025)
Changing lifestyles, tastes and product innovation make the food and beverage business a big opportunity in the Indonesian market. This large market opportunity has been crowded with competition between local products and foreign products, due to technological advances, and globalization. Mixue is a franchise business from China that offers tea and ice cream beverage products with flavors and appearances that are favored by consumers, especially young people. Strong market competition for beverage products causes market players to use market strategies to be able to play in the market sustainably. Consumer satisfaction is one of the main marketing keys. The marketing strategy that food and beverage entrepreneurs must carry out to survive in the market is to always pay attention and maintain product quality and customer service quality. The purpose of this study was to analyze the effect of product quality and service quality on the level of Mixue consumer satisfaction. The research was conducted in Pasuruan Regency in three sub-district capitals where Mixue outlets are Purwosari, Pandaan and Sukorejo with a sample size of 100 people. The analysis method used is measurement with a Likert scale and analysis using logit regression. The results of the analysis show that product quality and service quality have a significant positive effect on customer satisfaction. Product quality and customer service are two things that companies must pay attention to so that their products are accepted in the market by consumers and maintain product sustainability in the market.